Viomen, Large Scale Sculpture | Installation - Volanakis, Adonis (My University, 2026)
Viomen, (site-specific large scale sculpture with ceramics), exhibition +9 curated by Kostas Prapoglou, Iera Odos 18-20, Athens, Greece.